2020
DOI: 10.2147/lctt.s258444
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Comprehensive Review of Contemporary Literature for Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors in Non-Small Cell Lung Cancer and Their Toxicity</p>

Abstract: Mutations in the epidermal growth factor receptor (EGFR) are common amongst those with non-small cell lung cancer and represent a major factor in treatment decisions, most notably in the advanced stages. Small molecule tyrosine kinase inhibitors (TKIs) that target the EGFR, such as erlotinib, gefitinib, icotinib, afatinib, dacomitinib and osimertinib, have all shown to be effective in this setting. Osimertinib, a third-generation EGFR TKI, is a favorable option, but almost all patients develop resistance at so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…In cases of EGFR mutation, it was proven in the AURA trial series that second-line osimertinib significantly improved survival outcomes. Without a meticulous approach to driver mutation detection, as well as case-by-case individualized diagnostics, many of the patients whose tumors harbor a T790M mutation might be misdiagnosed and mistreated [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases of EGFR mutation, it was proven in the AURA trial series that second-line osimertinib significantly improved survival outcomes. Without a meticulous approach to driver mutation detection, as well as case-by-case individualized diagnostics, many of the patients whose tumors harbor a T790M mutation might be misdiagnosed and mistreated [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with a tumor biopsy-confirmed T790M mutation, osimertinib was reported to reach a response rate of 61% and a median progression-free survival of 9.6 months [6]. An analysis of phase I and II AURA trials reported equal efficacy of osimertinib independently of whether the T790M assessment was performed on plasma or on tissue from EGFR mutant patients with disease progression according to RECIST during first-generation EGFR-TKI treatment [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Some genes that encode signaling proteins that are crucial for cellular proliferation and survival, such as epidermal growth factor receptor (EGFR) gene, had found to have many different mutations in tumor tissue, and these mutations are related to selection of appropriate therapy [5][6][7][8][9]. Some new therapeutic agents, such as the epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) ge tinib and erlotinib, can produce a response for only NSCLCs carrying an EGFR mutation [10,11]. Hence it is necessary to know whether the EGFR gene exist mutations or not before the patients take the EGFR-TKIs [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The agents are categorized as first generation reversible agents (gefitinib, icotinib and erlotinib), second generation irreversible agents (afatinib and dacomitinib) and third generation agents with activity against secondary resistance mutation (osimertinib) and are summarized in Table 1. [6][7][8][9][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Gefitinib, erlotinib, afatinib, dacomitinib and osimertinib are all approved by United States Food and Drug Administration (US FDA) for use in front-line setting for EGFR mutation-positive NSCLC. 33,34 Head-to-head comparison between first generation TKIs, gefitinib and erlotinib was performed in a phase 3 study and both drugs were noted to have similar efficacy and toxicity.…”
Section: Introductionmentioning
confidence: 99%